Serum Urea and Creatinine Levels in Nigerian Local Horses Naturally Infected with Babesia - U. M. Garba*, A. K. B. Sackey1, R. I. S. Agbede2, L. B. Tekdek1 and M. Bisalla3 (Pakistan Veterinary Journal, 2011)
To study the effects of Babesia infection on urea and creatinine serum samples were randomly collected from 253 Nigerian local (Arewa) breed of Royal stallions and their Arabian and Sudanese crosses from five towns in Niger state, Nigeria. These horses were categorized into 5 groups based on their infection status. Urea and creatinine was assayed using spectrophotometer. Collected fecal samples were analy- zed using simple floatation method. The result showed non significant difference in serum levels of urea and creatinine in the various categories of horses namely Babesia infected horses, mixed Babesia + gastro-intestinal parasites infected horses, gastrointestinal parasites infected horses, negative apparently healthy and negative apparently sick horses. It can be concluded that natural Babesia infection in Nigerian local horses does not alter serum urea and creatinine levels.